Tradisi Pandhalungan, Nilai Nusantara, dan Pertalian Kebudayaan di Masyarakat Jember - Muhammad Zamroni (Islam & Contemporary Issues, 2021)
Indonesia is a rich nation in culture side. The ethnic diversity, local culture, ethnicity, class, and religion, has formed a society distinctive in Indonesia, which made Indonesia has more distinctive features and peculiarities in its various forms than other nations in the world. In addition, the Indonesian people are known for their friendly attitude, helping character, preference of working together and working hand in hand. All these attitudes are coming from natural characters which exist in village communities, which very few belong to the urban community. The evidence that the understanding of Indonesian society is inclusive, moderate and humanist cannot be ignored, because the social culture that grows and develops in Indonesia teaches these traits and attitudes. In the context of rural Indonesian society, especially for Jember society, it is borrowing the term used by Pandhalungan is a cultural identity. "Pandhalungan" as an icon of Jember district with the intention of making Jember district as a container of the various cultures in Jember. Then, how does the concept of cultural acculturation and the Islam Nusantara side? In addition, is there any value of Islam Nusantara that has been integrated in the procession of pandhalungan tradition at Jember regency? It is considering that Indonesia has a majority Moslem population that raised the jargon of Islam in Indonesia that is the Islam Nusantara. Thus, the purpose of this study is to understand the concept of cultural acculturation and Islam Nusantara, and to know the values of the Islam Nusantara which is integrated in the procession of pandhalungan. This research is used descriptive qualitative method with data collection technique through interview and documentation. The results of the existence of pandhalungan occurred since the occurrence of mixing or marriage between cultures but not all of pandhalungan culture contains the Islam Nusantara’s values. So, the so-called pandhalungan is the result of the mixing of intercultural and only part of the pandhalungan culture that is integrated to the values of Islam Nusantara.